Anorectal malformation with long perineal fistula: one of a special type - Sen Li (Nature Portfolio, 2021)
Abstract The anorectal malformation with long perineal fistula is a rare anomaly in the spectrum of anorectal malformations. Aim of the study is to describe the series of patients with anorectal malformation with long perineal fistula and compare the outcome with patient with standard perineal fistula. From March 2012 to January 2019, 7 patients who suffered from anorectal malformation with long perineal fistula were retrospectively reviewed. Three were operated on primarily by our department, and 4 cases were re-operated after a perineal anoplasty repair performed elsewhere. Four were operated by laparoscopy assisted anorectoplasty, and 3 cases were repaired by posterior sagittal anorectoplasty. The follow-up outcomes were compared with 71 cases of normal perineal fistula (NPF) in the same period. 7 cases have been followed up for 0.5–4 years (M = 2.57 ± 1.26) after definitive surgery. Their bowel function score was lower than normal perineal fistula (SPF = 12, range: 5–18; NPF = 18.5, range: 18–20). Four cases underwent anorectomanometry. The incidence of rectoanal inhibitory reflex was lower in the special type group. (p = 0.14). Three cases of contrast enema using barium: 2 cases of colorectal dilatation and thickening changes, 1 case showed no obvious abnormalities. Anorectal perineal fistula should be examined by distal colostogram at preoperation. This should be altered in: When suspecting a case of anorectal malformation type long perineal fistula a preoperative contrast enema could give insight of the anatomy befor performing a anoplasty.